Caracterización de los materiales de subrasante en zonas no urbanizadas de la ciudad de Loja, aplicadas a obras de infraestructura vial en el polígono denominado - Argelia - Gualán Seraquive, Ángel Rodrigo (2014)
This thesis research project is aimed to know the properties of materials at the level of foundation subgrade in undevelopable areas Loja canton. The thesis project is comprised of four stages: first stage is comprised of the fieldwork, comprising polygon delineation study, location of pits, sampling and in-situ tests. The second stage is in laboratory analysis of the physical and mechanical properties of the soil; the third step comprises the interpretation and analysis of the results, in the fourth stage of geotechnical zoning map that is a function of the floor type classification is made, and the ability to support different types of soils.